Changes in vascular plant species composition, top-soil and seed-bank along coppice rotation in an Ostrya carpinifolia forest. (3rd March 2020) - Mei, Giacomo; Pesaresi, Simone; Corti, Giuseppe; Cocco, Stefania; Colpi, Cristiana; Taffetani, Fabio
Abstract: Ostrya carpinifolia forests are formations traditionally managed as coppice, with a high biodiversity that characterizes much of the Italian and Balkan low mountain and hill landscapes. Here, we analyze changes in vegetation, seed-bank, soil and litter at six different stages during the coppicing rotation and after 10 years of abandonment of an Ostrya carpinifolia forest located in the central Apennines. Data show that the dynamism characterizing this coenose during traditional coppice rotation alters after cessation of the management practices. Although from the phytosociological point of view all the forest stands belonged to the same association, the highest biodiversity was achieved in the early stages after cutting. This was ascribed to the canopy removal, which creates favourable conditions for the germination of pre-mantels and mantels species stored in the soil seed-bank, while suitable conditions for the nemoral flora are maintained around the tree stumps. In later years, a reduction of non-strictly forest species and an increase in the relative thicknesses of the more superficial top-soil horizons occurred, reaching the maximum around 18 years after cutting. With the abandonment, simplification of the top-soil morphology, total loss of seed bank viability and increase of open-environments species were observed.